Digital Leadership, Organizational Learning, and Patient Safety in South Sumatra Type C Hospitals - Bahrin, Baharudin; Bahrin, Syarifudin; Sumardi, Septi Ardianty; Selamat, Mohd Nasir; Baker, Rogis; Budiman (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Patient safety is an important component in healthcare, but its implementation in type C hospitals still faces substantial problems due to resources and equipment that do not meet standards. This study aims to analyze the role of digital leadership on patient safety thru the mediation of organizational learning in the context of Complex Adaptive Systems (CAS). This study uses a quantitative method with a cross-sectional design. Data were obtained from 597 healthcare professionals in 24 type C hospitals in South Sumatra using a standardized questionnaire. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the direct and indirect associations between variables. The research findings indicate that digital leadership has a substantial positive association with patient safety (β=0.265; p<0.01) and organizational learning (β=0.519; p<0.001). Organizational learning has a significant relationship with patient safety (β=0.608; p<0.001) and plays a major role as a mediator. The indirect contribution of digital leadership thru organizational learning has proven to be broader than its direct contribution. Digital leadership not only serves as the adoption of technology but also as a facilitator of systemic changes that enhance collective learning and organizational resilience. Type C hospitals need to adopt digital leadership as a strategic effort that combines technological, psychological, and cultural variables to build a sustainable safety culture.